1992
DOI: 10.1007/bf01186952
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical mapping of noradrenergic projections to the rat spinal cord with an antiserum against noradrenaline

Abstract: The mapping of noradrenergic innervation was performed in transverse and longitudinal sections of the adult rat spinal cord using noradrenaline immunocytochemistry. Noradrenergic fibres and terminals were distributed in the dorsal horn (mainly in the superficial part), in the vicinity of the different groups of motoneurons, and concentrated in the intermediolateral cell column and around the central canal. The ultrastructural study showed principally axodendritic synapses in the ventral horn and in the interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 71 publications
7
47
1
1
Order By: Relevance
“…3). This laminar distribution accords with anatomical studies that have demonstrated the greatest density of serotonergic raphe-spinal terminals in dorsal laminae in the rat (Jones and Light, 1992), whereas noradrenergic fibers predominate in intermediate laminae (Rajaofetra et al, 1992).…”
Section: Chemical Basis For Nrm-evoked Changes In Oxidation Currentsupporting
confidence: 89%
“…3). This laminar distribution accords with anatomical studies that have demonstrated the greatest density of serotonergic raphe-spinal terminals in dorsal laminae in the rat (Jones and Light, 1992), whereas noradrenergic fibers predominate in intermediate laminae (Rajaofetra et al, 1992).…”
Section: Chemical Basis For Nrm-evoked Changes In Oxidation Currentsupporting
confidence: 89%
“…17,21,22 By using an antibody raised against noradrenaline, a wide distribution of noradrenergic ®bers at all spinal levels has been described. 23 However, direct evidence of relationships between catecholaminergic ®bers and spinal neurons destined to the pelvic organs is lacking.…”
Section: Central Noradrenergic Pathwaysmentioning
confidence: 99%
“…There is evidence that the noradrenergic 72 and serotonergic 73 and partly dopaminergic 48 neurotransmission in the dorsal horn is principally nonsynaptic. Some systems in the spinal cord may be highly nonsynaptic.…”
Section: Ndn Mechanisms In the Spinal Cordmentioning
confidence: 99%
“…They discussed their ®ndings in regard to the role of the descending serotonergic systems in analgesia. Marlier et al 74 also calculated a non-corrected synaptic incidence, while Rajaofetra et al 72 and Ridet et al 49 have determined the synaptic incidence of serotonergic, noradrenergic and dopaminergic innervation of the spinal cord by two procedures: by counting synapses on single sections and then applying the correcting formula established by Beaudet and Sotelo, 75 and by counting synapses on serial ultrathin sections. All of these studies reveal a high nonsynaptic incidence.…”
Section: Ndn Mechanisms In the Spinal Cordmentioning
confidence: 99%